2021
DOI: 10.1021/acsomega.1c02697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sex Factor on Mouse Iodine Intake: Interactions between the Gut Microbiota Composition and Metabolic Syndromes

Abstract: Iodine plays a key role in maintaining thyroid homeostasis, which is influenced by hormones through almost all nucleated cells and is essential for growth and metabolism. The most common kinds of thyroid dysfunction, hypothyroidism and hyperthyroidism, are markedly related to iodine intake. In addition, the prevalence and incidence of hypothyroidism and hyperthyroidism are much higher in women than in men. However, the association between thyroid homeostasis and the gut microbiota is not yet completely clear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, in female mice, these values decreased in comparison to the control group. Subsequent analysis of intergroup fecal differences in mice revealed that iodine-supplemented female ICR mice exhibited higher abundance of Desulfovibrionaceae ( 49 ). Therefore, we postulate that the Desulfovibrionaceae family could potentially impact thyroid function through certain pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, in female mice, these values decreased in comparison to the control group. Subsequent analysis of intergroup fecal differences in mice revealed that iodine-supplemented female ICR mice exhibited higher abundance of Desulfovibrionaceae ( 49 ). Therefore, we postulate that the Desulfovibrionaceae family could potentially impact thyroid function through certain pathways.…”
Section: Discussionmentioning
confidence: 99%